Imaginaires de nature sauvage dans la théorie et la pratique de Gilles Clément - Camilla Barbero (Projets de Paysage)
A nature the traits of which are untamed and shapeless takes over brownfields, urban wastelands and urban interstices, and contradicts such images as those of the deserts and ruins produced by our technological power. This nature fascinates us; increasingly placed in the limelight it is vested with an ecological value. This research explores imaginary perspectives nourished by ancient memories of these new landscapes by conducting a case study of the poetic vision of the gardener and landscape architect Gilles Clément. It seeks to understand whether one may identify resonances of the sublime in the surprise Clément evokes when faced with the chaotic initiative and the impermanence of an inventive pioneering vegetation. This rhetorical and aesthetic concept of the sublime is looked at from a wider perspective. An anthropological approach provides new insights to help understand the complexity of our relations with the untamed dimension of nature, a troubling yet appealing revelation of a non-human element reigning over and perpetuating life.